2003
DOI: 10.2108/zsj.20.1477
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and Population Structure of the Japanese Wild Boar Sus scrofa leucomystax: Mitochondrial DNA Variation

Abstract: Phylogeographic characteristics and population structure of Japanese wild boar (Sus scrofa leucomystax) were investigated using mitochondrial DNA (mtDNA) sequence data. Sixteen Japanese wild boar haplotypes detected from partial sequences of the mtDNA control region (574-bp) from 180 Japanese wild boar specimens from 10 local populations on Honshu, Shikoku, and Kyushu islands and 41 haplotypes from other S. scrofa were analyzed using the neighbor-joining method. The Japanese wild boars were more closely relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 44 publications
(50 reference statements)
9
48
2
Order By: Relevance
“…The study suggested that three populations, L, M and N (WNK, EC and WC, respectively, in Ishibashi and Saitoh's study), became isolated from the K population (ENK in Ishibashi and Saitoh's study) on the eastern side of the river, resulting in two populations that retreated to different refugia during the last glacial period. A similar phylogeographic pattern has been observed in other large mammal species such as the Japanese macaque (Kawamoto et al, 2007), Japanese wild boar (Sus scrofa; Watanobe et al, 2003) and sika deer (Cervus nippon; Tamate et al, 1998;Nagata et al, 1999), all of which exhibit two mtDNA lineages, with the distributions of the haplotypes of each lineage separated in the Kinki region. Given these data, Ishibashi and Saitoh (2004) suggested that the black bear would also have two Japanese lineages, separated at the Yura River.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The study suggested that three populations, L, M and N (WNK, EC and WC, respectively, in Ishibashi and Saitoh's study), became isolated from the K population (ENK in Ishibashi and Saitoh's study) on the eastern side of the river, resulting in two populations that retreated to different refugia during the last glacial period. A similar phylogeographic pattern has been observed in other large mammal species such as the Japanese macaque (Kawamoto et al, 2007), Japanese wild boar (Sus scrofa; Watanobe et al, 2003) and sika deer (Cervus nippon; Tamate et al, 1998;Nagata et al, 1999), all of which exhibit two mtDNA lineages, with the distributions of the haplotypes of each lineage separated in the Kinki region. Given these data, Ishibashi and Saitoh (2004) suggested that the black bear would also have two Japanese lineages, separated at the Yura River.…”
Section: Introductionsupporting
confidence: 73%
“…The border between the Western and Eastern cluster areas of the black bear appears to be Lake Biwa, which is approximately 100 km east of the border that separates two major lineages identified in Japanese macaques (Kawamoto et al, 2007), Japanese wild boar (Watanobe et al, 2003) and sika deer (Nagata et al, 1999). The distinct lineages in wild boar are thought to have resulted from multiple migrations of the species from the Asian Continent to Japan across land bridges that repeatedly formed between the Korean Peninsula and Kyushu Island during past glacial periods (Watanobe et al, 2003). In contrast, the distinct lineages in sika deer appear to have resulted from migration from the west across the Korea-Kyushu land bridge and from the north across the Sakhalin-Hokkaido-Honshu land bridge (Tamate et al, 1998; Nagata et al, 1999).…”
Section: Phylogeographic Relationshipsmentioning
confidence: 99%
“…Haplotypes of the 574-bp mtDNA were used in neighbor-joining analysis [12], which was performed using the PHYLIP program package, version 3.572 [3]. Sixty-three previously reported haplotypes (accession nos: D42170-D42174, D42178-D42185, AB015087-AB015086, AB041465-AB041473, AB041474-AB041476, AB041479-AB041485, AB041487-AB041493, AB041495-AB041499, AB053623-AB053627, D42176, AB071706, AB071707 and AB055222) [6,10,11,14,15] were used as reference sequences in NJ analysis.…”
mentioning
confidence: 99%
“…The mtDNA D-loop region (572 to 574 bp) was amplified using two primers, mit112 and mit106 (Watanobe et al 2003). PCR products were purified using a QIAquick PCR Purification kit (Qiagen), as described by Ishiguro and Nishimura (2005).…”
Section: Dna Extraction and Mtdna Analysismentioning
confidence: 99%
“…Alignment of DNA sequences and phylogenetic analysis mtDNA sequences (572 to 574 bp) were aligned with haplotypes published previously (Hongo et al 2002;Watanobe et al 2003;Ishiguro and Nishimura 2005;Ishiguro et al 2008a) using Clustal W (gap opening penalty 15, gap extension penalty 6.66) (Thompson et al 1994). Genetic distance was estimated by the proportion (P)-distance method in the MEGA4 (Tamura et al 2007).…”
Section: Dna Extraction and Mtdna Analysismentioning
confidence: 99%